1981
DOI: 10.1093/oxfordjournals.aje.a113258
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Characteristics of Necrotizing Enterocolitis: A Population-Based Study

Abstract: The authors studied retrospectively the epidemiologic characteristics of necrotizing enterocolitis occurring among Georgia infants born during 1977 and 1978; 148 cases of necrotizing enterocolitis were identified. The highest incidence rate for necrotizing enterocolitis occurred among infants weighing 751-1000 g at birth and declined with increasing birth weight to less than 0.2 cases per 1000 live births among infants weighing more than 2500 g at birth. The overall incidence rate for blacks was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 0 publications
1
20
2
3
Order By: Relevance
“…Wilson et al evaluated 148 patients with NEC and they found that NEC was observed most frequently among newborns less than 1000 g (42%) (10). Amold et al (8) evaluated 128 premature newborns and they found that average gestational age was 32 weeks and average weight at birth was 1466 g. In our study, average birth weight was 1861±817 g. Actually, this value was higher than the previous studies for NEC.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Wilson et al evaluated 148 patients with NEC and they found that NEC was observed most frequently among newborns less than 1000 g (42%) (10). Amold et al (8) evaluated 128 premature newborns and they found that average gestational age was 32 weeks and average weight at birth was 1466 g. In our study, average birth weight was 1861±817 g. Actually, this value was higher than the previous studies for NEC.…”
Section: Discussioncontrasting
confidence: 51%
“…It is mainly observed in premature newborns (90%) but 10% of patients with NEC are term newborns (9). Mortality varies between 10 to 50% but by the help of latest developments in recent years, mortality rate is reduced to 28% in some centers (10). In this retrospective study, the characteristics of 39 preterm newborns undergone operation for NEC were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (27) evaluated 148 patients with NEC and observed the highest rates (42%) in babies who were below 1000 g. The frequency of NEC was found to be 39.0% in babies with a birth weight of 1000-1500 g, 3.8% in babies with a birth weight of 1501-2000 g and 0.11% in babies with a birth weight above 2500 g. Grade III-IV necrotizing enterocolitis was observed only in 2 subjects (2.1%) and this rate was lower than the rate found by NICHD Neonatal Research Network in 1996 (17). No statistically significant difference was found between the groups in terms of presence of necrotizing enterocolitis (p=0.010).…”
Section: Discussionmentioning
confidence: 99%
“…23 Infected amniotic fluid is also involved in the "two-hit hypothesis", which implies that intrauterine exposure to inflammatory stimuli may "prime" cells of the innate immunity and make them more reactive, so that, on encounter with inflammatory stimuli peri-or postnatally they, may react with exaggerated production of proinflammatory cytokines involved in the pathogenesis of NEC. 19 Prolonged rupture of membranes 114 Placental abruption 94,136 Antenatal doppler abnormalities 129,137,138 Multiple birth 82,129 Birth outside a perinatal centre 27,82 Vaginal delivery 139 Cesarean section 29 Meconium aspiration 106 Asphyxia/Low Apgars 82,97,106,114,125,138,139 Antenatal glucocorticoids 138,139 Surfactant 123 African American descent 25,84,140 Male sex 125,136,140,141 Small for Gestational Age 28,[142][143][144] Congenital digestive, musculosceletal, or multiple anomalies 27,82 Congenital cardiovascular abnormality 82,87,93,106,112,…”
Section: Pathophysiologymentioning
confidence: 99%
“…In populations not restricted to a particular range of gestational age or birth weight, mortality rates of 12 to 38,5% have been reported 25,28,84,85,140,201,207,208 with seemingly lower rates in later publication years. After surgical treatment, mortality may be considerably higher.…”
Section: Outcomementioning
confidence: 99%